(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The Fourth Industrial Revolution is a new phase in industrial development that relies on the integration of advanced digital technologies such as artificial intelligence, the Internet of Things and data. The research aims to assess the readiness of the Cotton Factory, affiliated to the General Company for Textile and Leather Industries, to adopt the concepts and technologies of the Fourth Industrial Revolution (4.0), by adopting a checklist as a tool for collecting data and the IMPULS model as a framework for assessing the factory’s readiness for the digital transformation of its operations, focusing on the dimensions (strategy, smart factory, employees, smart operations, smart products, data-based services) to measure the company’s readiness for the Fourth Industrial Revolution, and using the Excel program to determine the level of readiness and the gap. The most important results showed that the Cotton Factory is at the first beginner level with an average of (1.160) and a gap of (2.84) and that the Cotton Factory has a technical infrastructure of the beginner type, but it needs improvement and development in some aspects to meet the requirements of the Fourth Industrial Revolution. It was noted that there is a weakness in the factory’s ability to collect and analyze data effectively, which hinders data-based decision-making. The message recommends the need to develop a comprehensive strategic plan to adopt the technologies of the Industrial Revolution. Fourth, focusing on enhancing the factory’s competitiveness and making the most of modern innovations.